Rancang Bangun Smart Home Berbasis Internet of Things - Mardawia Mabe Parenreng; Reski Damayanti; Asriyadi Asriyadi (Indonesian Society of Applied Science (ISAS), 2020)
Technological developments continue to develop rapidly until the generation of the Internet of things (IoT). IoT is a collection of objects, in the form of physical devices (hardware / embedded systems) that can exchange information between operators or other devices connected to the system. One of the benefits that can be felt is a smart home or smart home, which is a term used to describe a modern residence, with remote control such as controlling electronic goods. This control is intended for savings in electricity use. By using the ESP32 which functions as a liaison between the device and the internet network so that electronic goods that are available from home can be controlled by using an application installed on the smartphone. Based on tests carried out for the same network with a distance of 20 meters the device is successfully controlled, namely turning on and off the electronic device with a response time of 5s for the fastest time and 40s for the longest time, then for different networks, the control can still be done. So that with this smart home application, electricity costs can be saved.